Pre-hospital rule-out of non-ST-segment elevation acute coronary syndrome by a single troponin: final one-year outcomes of the ARTICA randomised trial - Aarts, Goaris W A; Camaro, Cyril; Adang, Eddy M M; Rodwell, Laura; van Hout, Roger; Brok, Gijs; Hoare, Anouk; de Pooter, Frank; de Wit, Walter; Cramer, Gilbert E; van Kimmenade, Roland R J; Ouwendijk, Eva; et al. (European Heart Journal - Quality of Care and Clinical Outcomes, 2024)
Abstract Background and aims The healthcare burden of acute chest pain is enormous. In the randomized ARTICA trial, we showed that pre-hospital identification of low-risk patients and rule-out of non-ST-segment elevation acute coronary syndrome (NSTE-ACS) with point-of-care (POC) troponin measurement reduces 30-day healthcare costs with low major adverse cardiac events (MACE) incidence. Here we present the final 1-year results of the ARTICA trial. Methods Low-risk patients with suspected NSTE-ACS were randomized to pre-hospital rule-out with POC troponin measurement or emergency department (ED) transfer. Primary 1-year outcome was healthcare costs. Secondary outcomes were safety, quality of life (QoL), and cost-effectiveness. Safety was defined as a 1-year MACE consisting of ACS, unplanned revascularization, or all-cause death. QoL was measured with EuroQol-5D-5L questionnaires. Cost-effectiveness was defined as 1-year healthcare costs difference per QoL difference. Results Follow-up was completed for all 863 patients. Healthcare costs were significantly lower in the pre-hospital strategy (€1932 ± €2784 vs. €2649 ± €2750), mean difference €717 [95% confidence interval (CI) €347 to €1087; P < 0.001]. In the total population, the 1-year MACE rate was comparable between groups [5.1% (22/434) in the pre-hospital strategy vs. 4.2% (18/429) in the ED strategy; P = 0.54]. In the ruled-out ACS population, 1-year MACE remained low [1.7% (7/419) vs. 1.4% (6/417)], risk difference 0.2% (95% CI −1.4% to 1.9%; P = 0.79). QoL showed no significant difference between strategies. Conclusions Pre-hospital rule-out of NSTE-ACS with POC troponin testing in low-risk patients is cost-effective, as expressed by a sustainable healthcare cost reduction and no significant effect on QoL. One-year MACE remained low for both strategies.